Peptides as Versatile Regulators in Cancer Immunotherapy: Recent Advances, Challenges, and Future Prospects - Yu Lei; Jiacheng Liu; Yaowei Bai; Chuansheng Zheng; Dongyuan Wang (Pharmaceutics)
The emergence of effective immunotherapies has revolutionized therapies for many types of cancer. However, current immunotherapy has limited efficacy in certain patient populations and displays therapeutic resistance after a period of treatment. To address these challenges, a growing number of immunotherapy drugs have been investigated in clinical and preclinical applications. The diverse functionality of peptides has made them attractive as a therapeutic modality, and the global market for peptide-based therapeutics is witnessing significant growth. Peptides can act as immunotherapeutic agents for the treatment of many malignant cancers. However, a systematic understanding of the interactions between different peptides and the host’s immune system remains unclear. This review describes in detail the roles of peptides in regulating the function of the immune system for cancer immunotherapy. Initially, we systematically elaborate on the relevant mechanisms of cancer immunotherapy. Subsequently, we categorize peptide-based nanomaterials into the following three categories: peptide-based vaccines, anti-cancer peptides, and peptide-based delivery systems. We carefully analyzed the roles of these peptides in overcoming the current barriers in immunotherapy, including multiple strategies to enhance the immunogenicity of peptide vaccines, the synergistic effect of anti-cancer peptides in combination with other immune agents, and peptide assemblies functioning as immune stimulators or vehicles to deliver immune agents. Furthermore, we introduce the current status of peptide-based immunotherapy in clinical applications and discuss the weaknesses and future prospects of peptide-based materials for cancer immunotherapy. Overall, this review aims to enhance comprehension of the potential applications of peptide-based materials in cancer immunotherapy and lay the groundwork for future research and clinical applications.